Teaching and learning quaternary prevention - Luís Filipe Gomes; Gustavo Gusso; Marc Jamoulle (Sociedade Brasileira de Medicina de Família e Comunidade, 2015)
This article presents an overview of different techniques and skills necessary for teaching and learning quaternary prevention (P4). It adopts the Expertise Model that defines the competences required in P4 for each level: novice, competent, proficient, and expert. This framework should be used as a step-wise roadmap for teachers in order to achieve high levels of performance. This proposal is complemented by a list of methods applied in teaching and assessment of learners' performance and competence. By covering a range of learning and teaching issues, those who aim to teach quaternary prevention can explore the proposed framework. Quaternary prevention is a research and teaching fertile medical field that entails the integration of different areas such as health service organisation, epidemiology, communication skills, and andragogy either at the macro or the micro levels of health related activities.